Invasive Liver Abscess Syndrome in the Immunocompromised: A Case Report - Amey Joshi; Eki Wari; Harith Ghnaima; Georgette Nader; Surya Chennupati; Nagham Jafar (Clinical Case Reports)
ABSTRACT Invasive liver abscess syndrome due to hypervirulent Klebsiella pneumoniae poses significant mortality risk, particularly in immunocompromised patients. Early recognition in non‐endemic regions is crucial for prompt antibiotic therapy and source control, highlighting the need for increased suspicion and aggressive management of this rare disease to improve patient outcomes.